2018
DOI: 10.3390/polym10121411
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Performance, Damping, and Surface Properties of Magnetorheological Elastomers via Particle-Grafting Technology

Abstract: A novel concept based on advanced particle-grafting technology to tailor performance, damping, and surface properties of the magnetorheological elastomers (MREs) is introduced. In this work, the carbonyl iron (CI) particles grafted with poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) of two different molecular weights were prepared via surface-initiated atom transfer radical polymerization and the relations between the PHEMATMS chain lengths and the MREs properties were investigated. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…For pure CI, saturation magnetization was 198 Am 2 /kg and CI/PGMA was 153 Am 2 /kg, respectively, confirming that the saturation magnetization is reduced by the coating of PGMA. Figure 6 b is the magnetization curve of CI particles coated with poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) [ 118 ]. It indicated that the saturation magnetization value decreased as the PHEMATMS coating thickness increased from 11 nm to 22 nm.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For pure CI, saturation magnetization was 198 Am 2 /kg and CI/PGMA was 153 Am 2 /kg, respectively, confirming that the saturation magnetization is reduced by the coating of PGMA. Figure 6 b is the magnetization curve of CI particles coated with poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) [ 118 ]. It indicated that the saturation magnetization value decreased as the PHEMATMS coating thickness increased from 11 nm to 22 nm.…”
Section: Characteristicsmentioning
confidence: 99%
“… ( a ) VSM curves of pure CI (open dark square) particles and PGMA coated CI (open blue circle) particles [ 60 ] and ( b ) magnetization curves of a—bare CI, b—CI-g-PHEMATMS-1 (11 nm), and c—CI-g-PHEMATMS-2 (22 nm) particles obtained via VSM [ 118 ]. …”
Section: Figurementioning
confidence: 99%
“…[40] Interestingly, research has recently been conducted elsewhere on magnetic elastomers with modified particle/ matrix interaction. [41] Prior to the present study, though, field-induced restructuring of magnetic nanofibers had not been previously explored in this context. Figure 9 shows low-field magnetic susceptibility, plotted as a function of magnetic field strength, for the PVB nanofibrous membranes with various MNP concentrations.…”
Section: Magnetic Properties Of the Membranesmentioning
confidence: 99%
“…Recently, Cvek at al. [23] fabricated two types of CI particles grafted with poly(trimethylsilyloxyethyl methacrylate) (PHEMATMS) of two different molecular weights. The results revealed that the PHEMATMS did enhanced the stability of CI particles and prevented the degradation in an acidic condition.…”
Section: Introductionmentioning
confidence: 99%